Pengaruh Kualitas Konten Netflix Original Squid Game terhadap Loyalitas Pelanggan di Pantai Indah Kapuk - Charlene Kwannaka; Rubiyanto . (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
The digital entertainment industry has experienced rapid growth alongside the increasing use of internet-based Over-The-Top (OTT) platforms. As a global streaming platform with a subscription-based business model, Netflix relies heavily on customer loyalty to sustain the continuity of its services. One of the strategies implemented by Netflix is the content production of Netflix Originals, one of which is the series Squid Game. Although previous studies have examined customer loyalty in streaming services, research that specifically highlights content quality as a factor influencing customer loyalty remains limited, particularly in the context of a single title with high audience expectations. This study aims to examine the effect of the content quality of the Netflix Original Squid Game Season 3 on customer loyalty with customer satisfaction as an intervening variable based on Expectation–Confirmation Theory (ECT) among Netflix subscribers in Pantai Indah Kapuk. This research employed a quantitative approach using purposive sampling techniques involving 332 respondents who were Netflix subscribers and had watched the series. Data were analyzed using path analysis to examine direct and indirect effects, as well as the Sobel test to examine the mediation effect among variables. The results show that Netflix Original Squid Game Season 3 content quality has a positive and significant effect on customer loyalty both directly and indirectly through customer satisfaction. These findings support Expectation–Confirmation Theory (ECT), which explains that perceived performance of a service influences the formation of customer satisfaction, which in turn encourages customer loyalty toward streaming services such as Netflix.